2022
DOI: 10.3389/fninf.2022.876927
|View full text |Cite
|
Sign up to set email alerts
|

FN-OCT: Disease Detection Algorithm for Retinal Optical Coherence Tomography Based on a Fusion Network

Abstract: Optical coherence tomography (OCT) is a new type of tomography that has experienced rapid development and potential in recent years. It is playing an increasingly important role in retinopathy diagnoses. At present, due to the uneven distributions of medical resources in various regions, the uneven proficiency levels of doctors in grassroots and remote areas, and the development needs of rare disease diagnosis and precision medicine, artificial intelligence technology based on deep learning can provide fast, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…For OCT images, we have also applied a fusion network algorithm to the retinal lesion classification of choroidal neovascularization (CNV), diabetic macular edema (DME), drusen, and normal groups. The result showed that the developed fusion algorithm can significantly improve the performance of classifiers compared to traditional algorithms while providing a powerful tool and theoretical support to assist with the diagnosis of retinal OCT images ( 16 ).…”
Section: Development Of Artificial Intelligence Algorithmmentioning
confidence: 99%
“…For OCT images, we have also applied a fusion network algorithm to the retinal lesion classification of choroidal neovascularization (CNV), diabetic macular edema (DME), drusen, and normal groups. The result showed that the developed fusion algorithm can significantly improve the performance of classifiers compared to traditional algorithms while providing a powerful tool and theoretical support to assist with the diagnosis of retinal OCT images ( 16 ).…”
Section: Development Of Artificial Intelligence Algorithmmentioning
confidence: 99%
“…By detecting patterns and anomalies in the data that human doctors may miss, AI can inform clinical decision-making and suggest potential treatments. Additionally, AI can predict the likelihood of a patient developing a particular disease or condition, allowing doctors to take preventive measures to reduce the risk of future complications [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…It can segment and detect vasculature (Fig. 2.A), shadowing artifacts, perfused areas, and even diagnose the severity of the disease state [21][22][23]. In biomedical engineering, AI is also being used to enhance the performance of optical instruments and instruments used in research.…”
Section: Biomedical Researchmentioning
confidence: 99%
“…Zhuang Ai et al [ 66 ] proposed a fusion network (FN)-based algorithm for the classification of retinal optical coherence tomography (OCT) images. The FN-OCT algorithm combines the InceptionV3, Inception-ResNet, and Xception deep learning algorithms with a convolutional block attention mechanism and three different fusion strategies to improve the adaptability and accuracy of traditional classification algorithms.…”
Section: Analysis Of Optical Coherence Tomography Imagesmentioning
confidence: 99%